Role of Industrial Relations in Public Sector Enterprises-The Indian Scenario - Sharma, Somya (Journal of Commerce and Trade, 2014)
The relationship between labour and management became very complex and neither party had any faith or confidence in each other. The big business concerns growing at a fast pace, the labour problems demanded an intelligent solution. Now, we have different labour enactments and judicial decision, which play a major role in regulating industrial relations. For maintaining harmonious labour management relations and for creating a climate of mutual confidence and trust between management and employees, public sector was expected to serve as a model employer and pace maker for rest of the economy. Now, it had to fight for itself for its very survival against the global giants on its own. Against this backdrop, we can proceed to analyse the significance of the present study. With the winds of change sweeping across the length and breadth of our country, the industrial relations (IR) situation cannot possibly remain a mute spectator to such nation-wide transition. IR in future may move in the direction of com radeship between the two main IR protagonists — management and trade union. With the terms of debate already showing signs of drastic change, IR in future will be governed by a totally new set of parameters. There is gradual realization by both the partners that to survive, both have to surrender their sectional interests at the alter of the superordinate interest of the economy.